Using the current Brazilian value for the biological exposure limit applied to blood lead level as a lead poisoning diagnostic criterion - Ricardo Cordeiro
In general, biological exposure limits are only used for the promotion and preservation of workers' health and are not applied for diagnostic purposes. However, the issue is controversial for certain types of occupational poisoning. This paper proposes the utilization of biological exposure limits currently applied to blood lead levels in Brazil as an important criterion for diagnosing occupational lead poisoning. The author argues that contrary to the traditional clinical criterion, one should deal with the diagnostic problem of lead poisoning from an epidemiological perspective, using the current Brazilian value for the biological exposure limit applied to blood lead level as an indicator of high relative risk.